Exploring the Impact of Humanistic Theory on Arabic Language Learning at MIN 2 East Lampung - Bima Fandi Asy'arie; Suci Zuhri Nurfadila Rahma; Zainul Fuat (Diwan Media Pustaka, 2024)
The humanistic theory is to see man as a free being with all the potential that exists within him. This study aims to know the current learning process and analyze the characteristic forms of humanistic theory implemented in Arabic language learning. This type of research is a qualitative descriptive approach. This research was conducted at MIN 1 East Lampung based on this information. Data collection techniques from observation, interviews and documentation. Then, for data analysis, namely data reduction, data presentation, and conclusions. The results of this study show that teachers already have humanist characteristics, including (1) Providing learning materials systematically, (2) Providing an attitude of affection and gentleness, (3) Providing freedom for students to learn while in class, (4) Providing motivation during the learning process, (5) Providing a fair attitude, (6) Giving awards for achievements that have been obtained. Thus, the learning process that prioritizes this humanistic approach is a pending step toward improving education. Because this approach can make students appreciate differences, have their own freedom of thought, and have the freedom to voice their opinions.